THE EFFECT OF INFRARED AND MUSCLE ENERGY TECHNIQUE ON INCREASING JOINT RANGE OF MOTION IN PATIENT WITH POST OPEN REDUCTION INTERNAL FIXATION 1/3 DISTAL HUMERUS PATIENTS: A RESEARCH ARTIKEL - Hidayati, Atik; Santoso, Totok Budi (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Fractures occur in individuals of all ages. However, the type and location of the body varies greatly depending on different factors, mainly related to the quality of the individual bone and the nature of the trauma. The population over 50 years of age in Sweden is expected to increase by 18% between 2010 and 2025, and it is estimated that the number of faults will increase by 26% during this time. The highest incidence of fractures recorded in the data are fractures of the clavicle, tibia, and fractures of the humerus. Case presentation: Immobilization after a fracture of the distal humerus will cause limited mobility of the elbow joint due to stiffness. A 10-year-old boy named An.AN was diagnosed with joint stiffness and postoperative pain . Implementation and results: The provision of infrared and muscle energy techniques in the case of joint stiffness of the distal 1/3 of the distal humerus is very necessary to reduce pain both at rest, motion, and pressure as well as to increase the range of motion of the joint and improve the limited functional ability of the elbow. Discussion: This study was conducted for 4 weeks and was carried out 2 times a week to receive infrared intervention and muscle energy technique. Infrared is given for 15 minutes in the elbow area and muscle energy technique with post isometric relaxation to reduce pain and increase the range of motion of the elbow joint. This study is expected to provide many advantages for this case. Conclusion: the provision of infrared and muscle energy techniques that are carried out twice a week for 4 weeks can be given to patients with postoperative joint stiffness to increase joint range of motion and improve function.